Morphometric and Meristic Diversity in Eel (Anguilla bicolor) in South Coast of Java - Endah Rochmatika; Win Darmanto; Mufasirin Mufasirin; Ramadhana Ramadhana (Journal of Aquaculture and Fish Health, 2023)
Indonesia is the largest exporter of eel to consumer countries such as European, America, Taiwan, Japan, South Korea, and the Middle East. Eels are catadromous fish that are in the growth phase in fresh waters and the development phase is in marine waters. Meristic measurement is done by counting the spine (vertebrates). Eel morphometric measurements include TL (Total Length), HL (Head Length), PDL (Pre-Dorsal Length), PAL (Pre-Anal Length) and ADL (Ano-Dorsal Length). The purpose of this study was to analyze the morphological, morphometric, and meristic diversity of intraspecies between populations. Based on the research, the samples identified were morphologically almost the same between the populations, this was seen from the color patterns in the form of plain black or brown and short fins. The morphometric and meristic measurements in the 3D distribution plot still appear to be clustered in one population, while in the dendrogram clade, one species is still congregated in each. The results of the interpretation of the matrix plot of the lowest diversity are the length and number of anodorsal vertebrate segments. This observation can be concluded that the TL and TV of the eel varied, while the PDL, PAL, PDV, PAV, ADV showed the intraspecies character of A. bicolor. This is because the distribution of A. bicolor eels that inhabit the waters of Java Island is widely distributed and random (panmitic).